2009
DOI: 10.1093/brain/awp220
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms ‘unexplained by organic disease’ in 1144 new neurology out-patients: how often does the diagnosis change at follow-up?

Abstract: It has been previously reported that a substantial proportion of newly referred neurology out-patients have symptoms that are considered by the assessing neurologist as unexplained by 'organic disease'. There has however been much controversy about how often such patients subsequently develop a disease diagnosis that, with hindsight, would have explained the symptoms. We aimed to determine in a large sample of new neurology out-patients: (i) what proportion are assessed as having symptoms unexplained by diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
201
1
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 299 publications
(224 citation statements)
references
References 24 publications
10
201
1
12
Order By: Relevance
“…Whilst there is debate on how these research criteria could be utilised in clinical practice (9), they can be used as a basis for diagnosing those patients who come to the memory clinics but who do not fit criteria for a memory complaint compatible with a neurodegenerative aetiology. Patients with functional disorders are not exclusive to memory clinics, and are commonly seen in general neurology clinics (10) . In a review of functional neurological symptoms by Carson and colleagues (11), it was noted that UK neurologists find these patients the hardest to treat (12).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there is debate on how these research criteria could be utilised in clinical practice (9), they can be used as a basis for diagnosing those patients who come to the memory clinics but who do not fit criteria for a memory complaint compatible with a neurodegenerative aetiology. Patients with functional disorders are not exclusive to memory clinics, and are commonly seen in general neurology clinics (10) . In a review of functional neurological symptoms by Carson and colleagues (11), it was noted that UK neurologists find these patients the hardest to treat (12).…”
Section: Introductionmentioning
confidence: 99%
“…Non-epileptic seizures (NES), also referred to as psychogenic non-epileptic seizures (PNES), is among the most common conditions with medically unexplained symptoms (MUS) within neurology [1]. However, qualitative research on NES is generally lacking [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 3,781 neurology patients in Scotland found that about 5% had a primary diagnosis of functional neurological symptoms, such as non-epileptic attacks, functional weakness and movement disorder. 2,3 Patients also present to specialties other than neurology with visual, 4 hearing and speech symptoms (typically a whispering dysphonia).…”
Section: How Common?mentioning
confidence: 99%